Effect of Corporate Governance on Cash Holdings of Nepalese Enterprises - Shrestha, Surakshya; Bhattarai, Sushil; Pokhrel, Sandeep; Oli, Tilak; Rawat, Ramesh (Nepalese Journal of Economics, 2025)
The study examines the effect of corporate governance on cash holdings of Nepalese commercial banks. The dependent variables selected for the study are cash flow from operating activities and cash flow from investing activities. The selected independent variables are board size, female directors, independent directors, audit committee size, firm size and foreign ownership. The study is based on secondary data of 12 commercial banks with 108 observations for the study period from 2014/15 to 2022/23. The data were collected from Banking and Financial Statistics published by Nepal Rastra Bank, publications and websites of Nepal Rastra Bank (NRB) and annual reports of the selected commercial banks. The correlation coefficients and regression models are estimated to test the significance and importance of corporate governance on cash holdings of Nepalese commercial banks. The study showed that board size has a positive effect on cash flow from operating activities and cash flow from investing activities. It means that higher the number of directors on the board, higher would be the cash flow from operating activities and cash flow from investing activities. Similarly, female director has a negative effect on cash flow from operating activities and cash flow from investing activities. It means that increase in proportion female directors on board leads to decrease in cash flow from operating activities and cash flow from investing activities. The results of the study also showed that audit committee has a negative effect on cash flow from operating activities and cash flow from investing activities. It implies that larger the size of audit committee, lower would be the cash flow from operating activities and cash flow from investing activities. Likewise, independent director has a negative effect on cash flow from operating activities and cash flow from investing activities which indicates that higher number of independent directors leads to decrease in cash flow from operating activities and cash flow from investing activities. However, foreign ownership has a negative effect on cash flow from operating activities and cash flow from investing activities. It implies that higher proportion of foreign ownership leads to decrease in cash flow from operating activities and cash flow from investing activities. Similarly, firm size has a positive effect on cash flow from operating activities and cash flow from investing activities. It implies that increase in firm size leads to increase in cash flow from operating activities and cash flow from investing activities.